An Analysis of Inclusion of Students with Disabilities in State Standards Documents. Technical Report 19 - Thurlow, Martha; Ysseldyke, James; Gutman, Sara; Geenen, Kristin; National Center on Educational Outcomes, Minneapolis, MN.; Council of Chief State School Officers, Washington, DC.; National Association of State Directors of Special Education, Alexandria, VA. ([Washington D.C.] : Distributed by ERIC Clearinghouse, 1998)
This report discusses findings from a study that examined the inclusiveness of state standards for students with disabilities. Specifically, the study investigated the extent to which individuals who know students with disabilities were involved in the development process, the extent to which students with disabilities were identified as being a target group of students for the standards, and the extent to which the standards represent broad domains of learning. These analyses revealed that while most states indicate that their standards are for "all" students, only 13 states specifically state that "all" includes students with disabilities. Furthermore, rarely were individuals knowledgeable about students with disabilities involved in the development of standards. Only eight states indicated specifically that these individuals were included in standards development. Finally, state standards covered many areas beyond academics; however, states almost exclusively focused their assessments on academics. Recommendations are presented and include: (1) standards should apply to all students, including those with disabilities and standards documents should clearly state that this is so; (2) accommodations should be provided to allow students who need them to reach standards; and (3) special educators should be involved in standards development. Appendices include relevant data charts. (Contains 18 references.) (Author/CR)
Availability: National Center on Education Outcomes, University of Minnesota, 350 Elliott Hall, 75 East River Road, Minneapolis, MN 55455; Tel: 612-624-8561; Fax: 612-624-0879; Web site: http://www.coled.umn.edu/NCEO ($10).
Sponsoring Agency: Special Education Programs (ED/OSERS), Washington, DC.
Contract Number: H159C50004.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Academic Standards; Accountability; Data Collection; Disabilities; Educational Assessment; Elementary Secondary Education; Input Output Analysis; Outcomes of Education; School Effectiveness; Special Education; Special Education Teachers; State Programs; State Standards; Student Participation; Teacher Participation; Test Construction; Reports, Research